The global burden of hypertension and its epidemiological impacts on adolescents and young adults: projections to 2050 - Niu, Chaofeng; Zhang, Peiyu; Wei, Lan; Dong, Juwei; Xu, Chenxi; Yang, Qiwen; Lyu, Diyang; Li, Nan; Li, Meng; Zhang, Lijing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo deeply analyze the epidemiological characteristics of the disease burden of hypertension and its related damages among adolescents and young adults aged 15–39 globally from 1990 to 2021, and predict the trends until 2050, providing key evidence for formulating global public health strategies.MethodsThe research data were derived from the Global Burden of Disease (GBD) 2021 database. The epidemiological trends of hypertension were systematically analyzed based on dimensions such as country/region, age, gender, and Socio-demographic Index (SDI). The age-standardization method was used to eliminate the influence of age-structure differences. Multiple statistical methods, including creating global maps, regional comparative analysis, and Joinpoint regression analysis, were employed to explore the distribution and change trends of the disease burden. The Bayesian Age to Period to Cohort (BAPC) model was utilized to predict future trends.ResultsFrom 1990 to 2021, the absolute numbers of hypertension-related deaths, Disability-Adjusted Life Years (DALYs), and Years Lived with Disability (YLDs) increased significantly globally. The age-standardized mortality rate and DALY rate decreased to some extent, while the YLDs rate increased slightly. There were significant differences in the hypertension burden across different regions, countries, SDI regions, genders, and age groups. Predictions indicate that by 2050, the age-standardized mortality rate and DALY rate will generally show a downward trend, while the age-standardized YLDs rate will continue to rise.ConclusionThe burden of hypertension among the global population aged 15–39 is severe and complex, affected by multiple factors. This study provides important reference directions for global public health efforts. In the future, it is necessary to strengthen international cooperation and develop targeted prevention and control strategies to reduce the burden of hypertension-related diseases among adolescents and young adults and promote the healthy development of youth worldwide.